Mammary analogue secretory carcinoma: a rare salivary gland tumor - Pol, Shashikant Anil; Singhal, Surinder K.; Gupta, Nitin; Bayad, Himanshu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Mammary analogue secretary carcinoma are salivary gland tumors similar to secretary carcinoma of breast histologically. It usually affects adults with mean age group of 45 years. Clinically it is usually slow growing, low grade malignancy with favorable prognosis. We are reporting a case of 47 years old female presented with complaints of swelling behind left ear for last 7 years. It was slow growing, painless and persistent. On examination, 4 x 3 cm swelling was present just below left ear lobule. It was nontender, firm, irregular in shape with smooth surface with slight mobility and overlying skin pinchable. Fine needle aspiration cytology suggested benign tumor with cystic change. On contrast enhanced computed tomography scan, there was a lobulated hypodense lesion measuring 24×35×32 mm with internal septations and enhancement of wall in expected location of superficial as well as deep lobe of left parotid gland. Patient underwent left total conservative parotidectomy and histopathology came out to be secretory analogue mammary carcinoma. Subsequently she received post-operative radiotherapy. Patient is on regular follow up and disease free till date. Usually mammary analogue secretory carcinoma is a low-grade malignancy with good prognosis. Immunohistochemistry is confirmatory which shows positivity for S-100 protein and mammaglobin.